Theoretical wear research of conical friction bearing - Попов, Станіслав Вячеславович; Васильєв, Анатолій Володимирович; Леднік, Роман Анатолійович (Technology audit and production reserves, 2015)
The wear value of related parts of conical friction bearing from the action of not only axial but also radial load was determined in the article. It was found that the pressure on the bearing surface is divided by a hyperbolic dependence. This work is conducted in order to increase the working life of a conical bearings used in the composition of the mobile mortar mixer URZ-3,8. During the experiments, we were able to find an expression for the resulting efforts in conical bearing, determine the expression of wear value of related parts. It is concluded that the service life can be increased, affecting the geometry of conical pins and bearing inserts. Also it is necessary to determine the material that resistant to wear for the manufacture of friction parts of bearing assembly. This work is important because the life of each machine depends on durability of components and parts. As a result, increasing the durability of machine parts reduced the costs of parts and materials for their production, complexity of the operation, maintenance and repair, reduces the number of employees and the complexity of operation, maintenance and repair.